Evolutionary transition-transversion bias by the example of the cytb gene of palearctic Muridae (Rodentia) and Vespertilionidae (Chiroptera) - Mezhzherin, S.V.; Morozov-Leonov, S.Y.; Zhalay, O.I.; Kokodiy, S.V.; Tereshchenko, V.O.; Rostovskaya, О.V.; Tsyba, A.O. (Reports of the National Academy of Sciences of Ukraine, 2023)
A comparative analysis of the features of the transition-transversion bias of the nucleotide sequence of the cytb gene in microbats (Vespertilionidae, Chiroptera) and mice (Muridae, Rodentia) shows both general regularities and certain family-level features. A common feature of the two families is the fact of the sharp predominance of transitions over transversions at the early stages of the evolutionary process, followed by the equalization of the ts/tv-displace- ment at the species and genus levels of divergences, as well as the fact that the increase in the frequency of transitions in phyletic lineages is gradual, and the transition is intermittent. At the same time, the levels of spontaneous mutations and evolutionary drift, as well as the rate of ts/tv drift compensation, are specific to families. These circumstances do not make it possible to obtain comparable estimates of divergence in different phyla and cause insurmountable difficulties in creating a universal formula for molecular clocks.